Identifying Criteria and Indicators Correlating to the Decline in Psychological Well-Being of Homeless Women: A Systematic Review - Mirkamal Mirnasiri; Hossein Keshavarz Afshar; Abbas Rahiminezhad; Keyvan Salehi (پژوهش‌های کاربردی روانشناختی)
The objective of the current review research was to determine the criteria and indicators that are associated with the decline in the psychological well-being of homeless women. The research was practical in terms of its purpose and systematic review of data collection. The pertinent documents were reviewed in the domain of 2012 to 2024 by employing the specialized keywords of psychological health in homeless women, psychological injuries in homeless women, and Elsevier, Scopus, Web of Science, SID, Magiran, and Sage in domestic and foreign databases. The statistical population of this research consisted of 101 Persian and English articles that were identified through keyword searches. 33 documents were included in the final review of this research based on quality assessment criteria. The six-step thematic analysis method of Braun & Clarke (2006) was employed to analyze the data. The findings showed that in general, negative physical characteristics and related diseases, psychological problems, addiction and drug use, and emotional problems have a significantly higher prevalence in this group. Additionally, the results revealed that 42 indicators, including 8 criteria of attachment patterns, family relationships, personality traits, meaninglessness, trauma, physiological problems, environmental stimuli, and psychological problems, predicted low psychological well-being in homeless women. From the results, it can be concluded that homelessness is a phenomenon that is influenced by negative stimuli in an individual's family and social life.